IOU field reports form, Douglas C. Harr, July 29, 1988 - Harr, Douglas C.et al (1988)
List of birds and locations contributed by Douglas C. Harr. The field report includes information on a deceased Peregrine Falcon. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1988. Epson - sheet feed